Caso de estudio: IOI's global challenge: moving up the palm oil value chain - Buchhammer Arroyo, Jose Alonso (2019)
The objective of this case is to evaluate IOI Corporation Berhad, determing quantitatively the level of success and competitiveness that it has had during the period between 2012 and 2017. To achieve this, the group's performance was analyzed in the areas of market intelligence, international marketing, Strategy Global Management, international commerce logistics and international finance in the global palm oil industry. For this analysis, the differential characteristics of this case were considered due to the context in which the company is located. In the first place, IOI is a family business and because of this it has faced stigmatisms that suppose a company of this nature, but despite this it has remained professional and focused on differentiation strategies, unusual along this type of companies. However, the risks of falling into a nepotism that provides few efficiencies or the conservatism of company bosses remain latent. Secondly, this successful company has faced two crises in the last five years, affecting its financial sustainability and damaging its image, forcing IOI to examine its financial and communication strategies only to act reactively, when the company was already submerged in these events. Finally, and as already mentioned, IOI has invested vast resources in its differentiation strategy, acquiring Loders Croklaan for research, development of new products and their use within the palm oil industry, seeing this strategy as its most important added value against a global market which is certainly fragmented. It is for these reasons that the case of this company of Malay has important differential factors that will be measured in order to recommend what strategies should be followed to continue the internationalization of IOI.